Characteristics and Influencing Factors of Soil Erosion in Luoshan County, He'nan Province Based on Geological Formation - Yang Tao; Dong Haogang; Li Xin; Luo Minxuan; Wu Feng; Huang Jinyan; Xie Xiang (Shuitu baochi tongbao)
[Objective] The relationship between soil erosion of each formation unit and ecological geological characteristics was analyzed in order to provide a reference for soil erosion prevention and for control planning and restoration in Luoshan County, He'nan Province. [Methods] Based on the revised universal soil loss equation (RUSLE), soil erosion of main formation units in Luoshan County was calculated and counted by means of remote sensing and GIS, and the intensity and the area of soil erosion was determined. The influencing factors of soil erosion in a typical formation were then discussed from the perspectives of geological formation and characteristics. [Results] ① Due to differences in formation times, material compositions, and geological backgrounds, the eco-geological characteristics of each formation unit were different; ② The distribution of soil erosion in Luoshan County had obvious spatial differences. The soil erosion rate of the cretaceous acid magmatic rock formation unit was as high as 50.1%, while the soil erosion rate of the devonian metamorphic flysch formation unit was only 13.5%. [Conclusion] Soil structure, vegetation factors, and terrain slopes were important factors affecting the differences in soil erosion distribution, which should be considered in the planning of soil erosion prevention and rehabilitation.